Limestone, Gypsum, Palm Oil Mill Effluent and Rock Phosphate Effects on Soil Solution Properties of Some Malaysian Ultisols and Oxisols - Jusop, Shamsuddin; I., Jamilah; Abdul Hamid, Sharifuddin; Bell, L. C. (1992)
Ultisols and Oxisols in Malaysia are characterized by low pH, high Al saturation, low ECEC and Ca and/or Mg deficiencies, which are limiting to annual crop production. A pot experiment was conducted to assess the chemical changes in the properties of the soil solution phase of soils of some representative Ultisols and Oxisols following application of limestone, gypsum, palm oil mill effeluent and rock phosphate. The results showed that 2-4 t limestone/ ha were needed to increase pH, Ca, Mg and SO/, and to reduce Al and Mn to an acceptable level in the soil solution. Palm oil mill effluent application at 0.5-1 t/ha (lime equivalent) gave similar liming effects to those of limestone. Gypsum application increased Al concentration, but at high rate of application the Al existed mainly in the form of AISO/. Gypsum application in RPngam, Bungor and Prang series soils at 1 t/ha reduced pAIOHS0 4 to 17, suggesting that jurbanite can be formed in Ultisols and Oxisol when gypsum is applied.